NIGHT LIGHTS. - Choi, Jin-Woo (History Today, 2026)
The article focuses on how Enlightenment-era scholars sought to understand the aurora borealis by turning to historical records, linguistic clues, and earlier descriptions of celestial phenomena. Topics include the many cultural names and interpretations of the northern lights, the efforts of early modern scientists to trace auroral activity through medieval and classical sources, and the challenges of distinguishing genuine auroral sightings from superstition or symbolic imagery.